Selenium applications enhance 2‐acetyl‐1‐pyrroline biosynthesis and yield formation of fragrant rice. (14th January 2021) - Luo, Haowen; He, Longxin; Lai, Rifang; Liu, Jinhai; Xing, Pipeng; Tang, Xiangru
Abstract: Selenium (Se) is a beneficial element for plants and a necessary element for humans. Previous studies showed Se could increase 2‐acetyl‐1‐pyrroline (2‐AP) content in fragrant rice ( Oryza sativa L.), but the underlying molecular mechanism remains largely unexplored. There are several methods for Se application in rice production, and it is not clear which is better. This study investigated the effects of three different Se application methods on 2‐AP biosynthesis, yield formation, and grain Se concentration of fragrant rice through a four‐season field experiment with two fragrant rice cultivars. For soil application, Se was applied as Se mineral powder as basal application to soil (36 g Se ha −1 ); for foliar application (FA), sodium selenate solution (40 μmol L −1 ) was applied as a foliar spray at heading stage; and for seed priming, fragrant rice seeds were primed with sodium selenate at 80 mg kg −1 concentration. The treatment without Se was taken as control (CK). The results showed Se applications increased grain 2‐AP content and grain yield by 3.95–22.32% and 1.03–8.05%, respectively. Compared with CK, Se applications regulated transcript levels of genes PRODH, BADH2, DAO, OAT, and P5CS2, which are involved in 2‐AP biosynthesis. Selenium applications also increased the contents of precursors (Δ1‐pyrroline, proline and pyrroline‐5‐carboxylic acid) and enhanced the activities of enzymes (proline dehydrogenase, △1‐pyrroline‐5‐carboxylic acid synthetase, ornithine aminotransferase, diamine oxidase), which are related to 2‐AP. Furthermore, Se applications increased grain Se concentration by 14.12–63.25%. The highest grain yield, grain 2‐AP content, and grain Se concentration were all recorded in the FA treatment. Core Ideas: Se application improved yield formation of fragrant rice. Se application increased grain 2‐acety‐1‐pyrroline (2‐AP) content of fragrant rice. Se application regulated transcript level of genes related to 2‐AP biosynthesis. Foliar application of Se is the best application for fragrant rice production.